Challenges on innovation and performance studies in Costa Rican family-owned SMEs - Lezcano Calderón, Yendry (2026)
Family businesses represent a high percentage of the economy and it has been demonstrated that SMEs are dynamizers of economies, it is relevant to review in the light of theory the impact of networks on marketing innovation in family SMEs. Based on a literature review, we intend to propose future studies that will contribute to understand the effects of social and business networks on marketing innovation and, as a consequence, on the performance of family SMEs in Costa Rica. To this end, we will delve into network theory and social capital theory and how they converge in an impact on innovation strategies and financial and non-financial performance, organizational effectiveness and stakeholder satisfaction.